2013
DOI: 10.1542/peds.2013-0252f
|View full text |Cite
|
Sign up to set email alerts
|

Does Well-Child Care Have a Future in Pediatrics?

Abstract: The most common adult chronic diseases affect 1 in 3 adults and account for more than three-quarters of US health care spending. The major childhood drivers of adult disease are distinctly nonmedical: poverty, poor educational outcomes, unhealthy social and physical environments, and unhealthy lifestyle choices. Ideally, well-child care (WCC) would address these drivers and help create healthier adults with more productive lives and lower health care costs. For children without serious acute and chronic medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 90 publications
0
31
0
Order By: Relevance
“…The inclusion of nonphysicians as part of a team approach to care is widely recognized as a key component in preventive care quality improvement and WCC delivery system redesign. 13,[36][37][38] In a recent review of tools and strategies to improve WCC, we found evidence suggesting that inclusion of nonphysician providers into a health care team could improve receipt of anticipatory guidance and developmental and behavioral services. 16,17,[39][40][41][42] In Healthy Steps, a physician and child developmental specialist (typically a nurse, social worker, or early childhood educator) provide WCC in partnership.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The inclusion of nonphysicians as part of a team approach to care is widely recognized as a key component in preventive care quality improvement and WCC delivery system redesign. 13,[36][37][38] In a recent review of tools and strategies to improve WCC, we found evidence suggesting that inclusion of nonphysician providers into a health care team could improve receipt of anticipatory guidance and developmental and behavioral services. 16,17,[39][40][41][42] In Healthy Steps, a physician and child developmental specialist (typically a nurse, social worker, or early childhood educator) provide WCC in partnership.…”
Section: Discussionmentioning
confidence: 97%
“…[6][7][8][9][10][11] Key structural problems in WCC include: (1) reliance on highlevel clinicians (pediatricians, family physicians, and nurse practitioners) for basic, routine WCC services; (2) limitation to a clinician-directed wellvisit for the wide array of education and guidance services in WCC; and (3) lack of a systematic, patientdriven method for visit customization to meet families' needs. 1,2,[12][13][14][15] Various tools and strategies to redesign the structure of WCC have been proposed and studied; however, there are few evidencebased comprehensive models of care to serve as feasible and sustainable alternatives to the current WCC structure in most small community practices. 16,17 Our comprehensive model (ie, the Parentfocused Redesign for Encounters, Newborns to Toddlers [PARENT]) was developed to address these key structural deficiencies in our current WCC system by decreasing reliance on the physician for routine WCC and shifting many WCC services to a health educator.…”
mentioning
confidence: 99%
“…16,[18][19][20] With the advent of retail-based clinics and Internet-based care, 35 a greater burden of chronic disease during childhood, 36 and an increasing need for chronic care management, 37 primary care pediatrics may need to adapt to a more specialty-based model similar to primary care pediatrics in many other developed nations. 38,39 This study has several limitations. First, WCC models were designed specifically for practices involved in the study and may not be generalizable to others.…”
Section: Model 4: Technology-based Modelmentioning
confidence: 96%
“…The utility and viability of wellchild care in its present form has been called increasingly into question. 3 We need new ideas to create bigger positive change especially for the health and well being of low income children. The goal of this article is to call on present and future practicing and academic pediatricians to take on the challenge of innovation and change.…”
mentioning
confidence: 99%